12.29% Low Temperature–Processed Dopant‐Free CdS/p‐Si Heterojunction Solar Cells. Issue 12 (22nd May 2019) - Cai, Lun; Wang, Wenxian; Jin, Lei; Yao, Zhirong; Lin, Wenjie; Meng, Lanxiang; Ai, Bin; Liang, Zongcun; Huang, Yuelong; Zhang, Fuqin; Altermatt, Pietro P.; Shen, Hui
Abstract: Most crystalline silicon (c‐Si) solar cells are based on high temperature–processed p‐n junctions or highly doped heterojunctions. The concept of dopant‐free carrier selective contact has become a research hotspot and been successfully demonstrated with n‐type Si wafers, showing the great potential of simplified fabrication process and lower thermal‐consuming. However, there are few successful cases on p‐Si, dopant‐free p‐Si/CdS (cadmium sulfide)/ITO (indium tin oxide) solar cells with champion efficiency of 12.29% (device area 4 cm 2 ) have been demonstrated with DC magnetron sputtered CdS thin films working as electron‐selective contact. A proper annealing treatment is found essential in improving the p‐Si/CdS/ITO heterocontact and device performance. The author's preliminary results confirm the feasibility of preparation of efficient p‐Si wafer–based dopant‐free solar cells. Abstract : Most crystalline silicon solar cells are based on high‐temperature‐processed p‐n junctions or highly doped hetero‐junctions. Champion efficiency of 12.29% low‐temperature‐processed dopant‐free solar cells are demonstrated on p‐type wafer with magnetron sputtered cadmium sulfide (CdS) thin films working as electron‐selective contact. Annealing is found essential in improving the device performance.